The Effectiveness of Group Counseling Using Self-Counseling Techniques to Increase Students' Learning Motivation - Niswatul Baroroh; Eva Imania (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
Lack of motivation to learn influences the decline in student academic achievement and exam results, as experienced by class XII students at MAN 1 Deli Serdang, North Sumatra. This research aims to determine the effectiveness of group counseling services using the Counseling Self technique in increasing students' learning motivation. This is a type of quasi-experimental research with an unequal control group research design. The sample was determined using a purposive sampling technique, with respondents totaling 68 students in class XII MAN I Deli Serdang, North Sumatra. The results show that after being given treatment, namely group counseling services using the Self Counseling technique, in the experimental group, there was a significant increase in students' learning motivation. This can be proven by research results and the increase in students' academic results. From the results of research using self-counseling techniques where the higher the social support to increase students' learning motivation, it is hoped that BK teachers can provide guidance and counseling services using the self-counseling method to create and increase good learning motivation.